2012
DOI: 10.1007/s10103-012-1095-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different power outputs of intraoral Nd:YAG laser on shear bond strength of a resin cement to nickel–chromium dental alloy

Abstract: Up to now, there is no any experience about the application of dental lasers to bond resin composites to metal surfaces in dentistry. The aim of this preliminary study was to evaluate if the laser irradiation of ceramic-covered alloy surface would improve the bond strength of resin to metal, and if different parameters of laser output may influence the strength of this bond. Fifty three cylinders (thickness of 5 mm and diameter of 10 mm) were made up of a commercially available nickel-chromium alloy by lost-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Although our study found that laser application alone produced better results than the sandblasting application, this difference was not statistically significant ( p > 0.05). In a study conducted by Madani et al [40], it was found that the application of an Nd:YAG laser with 6 W or 8 W output power on the surface of the metal did not increase the bond of the resin cement to the metal and that the sandblasting application with Al 2 O 3 produced better results than the laser application. The decrease in the bond strength after the laser treatment has been explained by a change in the surface characteristics of the metal due to the laser application [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our study found that laser application alone produced better results than the sandblasting application, this difference was not statistically significant ( p > 0.05). In a study conducted by Madani et al [40], it was found that the application of an Nd:YAG laser with 6 W or 8 W output power on the surface of the metal did not increase the bond of the resin cement to the metal and that the sandblasting application with Al 2 O 3 produced better results than the laser application. The decrease in the bond strength after the laser treatment has been explained by a change in the surface characteristics of the metal due to the laser application [40].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Madani et al [40], it was found that the application of an Nd:YAG laser with 6 W or 8 W output power on the surface of the metal did not increase the bond of the resin cement to the metal and that the sandblasting application with Al 2 O 3 produced better results than the laser application. The decrease in the bond strength after the laser treatment has been explained by a change in the surface characteristics of the metal due to the laser application [40]. Additionally, in a study conducted by Kunt et al [41], it was found that the application of an Er:YAG laser did not increase the roughness of the metal surface in comparison to the group that had no surface treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike controversies mentioned for zirconium-based porcelains, the application of this laser for feldspathics was beneficial. 13,14 Erbium lasers: These groups of lasers consist of Er:YAG and Er,Cr:YSGG with irradiation wavelengths of 2940 nm and 2780 nm respectively; these lasers are best absorbed by water and hydroxyl apatite at the invisible spectrum. Although there are similarities between these two lasers, differences like wavelengths, tissue ablation ability, thermogenesis potential, and penetration depth make them distinct.…”
Section: 12mentioning
confidence: 99%
“…Some recent investigations, studied the effect of laser irradiation on the bond strength of resin restorative materials to ceramics. It has been reported that comparing with conventional sandblasting and acidetching techniques, there was no significant difference associated with the Er:YAG or Nd:YAG laser application to bond the resin cements to the dental porcelain, so treatment of porcelain surface with laser may be as effective as conventional methods ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Madani, A et al evaluated the effect of irradiation using a Nd:YAG laser on ceramic-covered alloy surface and hypothesized if it would improve the bond strength of resin to metal, and if different parameters of laser output may influence the strength of this bond, they concluded that shear bond strength was significantly higher in porcelain-covered laser treated samples, but the effect of power output of laser irradiation was not significant they further concluded that Nd:YAG laser surface treatment may improve the silica coating of alloy surface to achieve better resin–metal bond ( 8 ). Another study concluded that laser etching of titanium surfaces using an Nd: YAG laser was effective in improving bond strength with low-fusing porcelain, as compared to the acid-etching method ( 10 ).…”
Section: Discussionmentioning
confidence: 99%